2020
DOI: 10.1055/s-0041-1723778
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Personalized Risk-Stratified Approaches to Treatment for Gestational Diabetes: A Narrative Review

Abstract: Gestational diabetes mellitus (GDM) is common and is associated with an increased risk of adverse pregnancy outcomes. However, the prevailing one-size-fits-all approach that treats all women with GDM as having equivalent risk needs revision, given the clinical heterogeneity of GDM, the limitations of a population-based approach to risk, and the need to move beyond a glucocentric focus to address other intersecting risk factors. To address these challenges, we propose using a clinical prediction model for adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In alignment with the literature, our findings indicated that there is a need for GDM care to be provided in a manner that is comprehensible, personalized and accessible, to best accommodate the lifestyle choices of diverse patient populations 30,34 . In particular, our study highlighted the importance of knowledge sharing as a facilitator in the decision‐making process 14,29,30,35 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In alignment with the literature, our findings indicated that there is a need for GDM care to be provided in a manner that is comprehensible, personalized and accessible, to best accommodate the lifestyle choices of diverse patient populations 30,34 . In particular, our study highlighted the importance of knowledge sharing as a facilitator in the decision‐making process 14,29,30,35 .…”
Section: Discussionsupporting
confidence: 78%
“…17,33 In alignment with the literature, our findings indicated that there is a need for GDM care to be provided in a manner that is comprehensible, personalized and accessible, to best accommodate the lifestyle choices of diverse patient populations. 30,34 In particular, our study highlighted the importance of knowledge sharing as a facilitator in the decision-making process. 14,29,30,35 Knowledge sharing is a reciprocal process that promotes patient empowerment, and encourages humility of the provider to foster a relationship built on mutual respect and rapport.…”
Section: Discussionmentioning
confidence: 72%
“…The deleterious role of hyperglycemia during pregnancy has been further demonstrated by intervention studies in which "near normal" maternal blood glucose levels led to a decrease of adverse events (8,9). These observations have led to a "glucocentric" approach of diabetes care in pregnancy, that is too restrictive (10), and other potentially modifiable risk factors have been identified, such as pre-pregnancy obesity, excessive weight gain during pregnancy, and gestational hypertension (11)(12)(13). Recent studies also showed that in women with gestational diabetes, beyond the degree of hyperglycemia, the respective roles of insulin deficiency and insulin resistance in the pathophysiology of mother's diabetes may have differential impacts on pregnancy adverse events (14,15).…”
Section: Diabetes In Pregnancymentioning
confidence: 99%
“…12 We need a robust risk-based approach to plan the management of women with GDM, enabling shared decision-making and more personalised care. 13 The accurate identification of women with GDM at highest risk of adverse pregnancy outcomes would facilitate their targeted management with high intensity care, while those identified to be at low risk of complications can be managed within routine care pathways, or potentially in the community. Previous models to predict the risks are hampered by statistical methodological limitations which limit generalisability, such as inadequate power, dichotomisation of continuous predictor variables and predictor selection dependent on associations with the outcome in the development dataset.…”
Section: Introductionmentioning
confidence: 99%